New species and a new record of Capniidae (Plecoptera) from Xinjiang Uygur Autonomous Region of northwestern China - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2017)
Two new winter stoneflies (Capniidae), Capnia trispinosa Chen & Du sp. nov. and Isocapnia apicispina Chen & Du sp. nov. are described from Xinjiang Uygur Autonomous Region of northwestern China. Capnia trispinosa sp. nov. is characterized by the main epiproct sclerite with three large dorsal spines. Isocapnia apicispina sp. nov .is characterized by its dorsal apex of main epiproct sclerite truncated with denticulate lateral margins and by having a ventroapical spine on epiproct. The new species are compared with similar taxa. Additionally, the widespread Palearctic C. nigra (Pictet, 1833) is reported for the first time for China from the Xinjiang Uygur Autonomous Region.